The NSF Convergence Accelerator program. Issue 1 (31st March 2022) - Baru, Chaitanya; Campbell, Lara; Dade, Aurali; Fulay, Pradeep; Loewi, Alex; Maughan, Douglas; Mohedas, Ibrahim; Molnar, Linda; Pozmantier, Michael; Reksulak, Michael; Smith, Shelby; Tehrani, Nicole
Abstract: The National Science Foundation's Convergence Accelerator is a unique program offering researchers and innovators the opportunity to translate research results into tangible solutions that make a difference for society. Through an intense innovation curriculum and a mentorship program, researchers gain skills and experiences that are of use not only during this program but throughout their careers. This article describes the NSF Convergence Accelerator program and its initial funded convergence research topics—or "tracks"—funded in 2019 and 2020. In almost every track and NSF‐funded project, artificial intelligence and machine learning (AI/ML) approaches and methods are playing an essential role.